P741 Do gastroenterology services need published standards for provision of antenatal care in patients with Inflammatory Bowel Disease? A local evaluation of UK practice. (30th January 2023) - Tolan, M; Nartey, J; Dattoo, M; King, D; de Silva, S
Abstract: Background: Inflammatory bowel disease (IBD) is common with 0.5-1% of the UK living with the disease. Poor disease control can result in adverse pregnancy outcomes including low birth weight and preterm labour. It is essential that pregnant patients with IBD receive care from physicians experienced in management of antenatal IBD. Furthermore patients must be equipped with the knowledge to make decisions on their care and the care of their new-born. Audit standards by Selinger et al 20201 for the British Society of Gastroenterology (endorsed by the British Maternal and Fetal Medicine Society) have been published for UK practice but local service standards are unknown. Methods: Pregnant patients with Crohn's disease (CD) and Ulcerative Colitis (UC) between 2017-2020 were identified with ICD-10 and OPSC-4 codes for a hospital with 650 inpatient beds and a catchment area of 450, 000 with around 4, 600 births per annum. The service was assessed against a 90% compliance standard for documentation of: a decision on biological therapy during pregnancy; discussion on mode of delivery (MoD); antenatal live vaccine counselling; and breast-feeding advice. Results: 48 eligible patients were identified. Mean birth weight and delivery date were in line with the national average with no preterm births. 41 of 48 patients (85%) were in remission at the time of conception. 9 of 25 CD pregnancies were on biologics at conception and 7 of 9 (78%) discontinued this by 24-weeks gestation; one continued vedolizumab to 30-weeks and received antenatal vaccine counselling; one continued ustekinumab to 34-weeks. 4 out of 23 UC pregnancies were on biologics at conception; all ceased biologics by 24-weeks and vaccine counselling was not indicated. Only one published standard was achieved, with decision on biologics in pregnancy discussed in 100% (13/13). 3 standards were not met; MoD discussion (23%, 11/48); antenatal vaccine counselling (50%, 1/2); and breast-feeding advice (4%, 2/48). Conclusion: Our service did not meet new standards for antenatal IBD care, demonstrating a need for improvement. We recommend that all IBD teams understand the expected service standards, perform a baseline service evaluation and develop clear patient pathways and departmental guidelines to identify pregnant patients with IBD. Clear patient information and close collaboration between obstetricians and gastroenterologists is essential to optimise the outcome for mother and baby. 1) Selinger C et al Standards for the provision of antenatal care for patients with inflammatory bowel disease: guidance endorsed by the British Society of Gastroenterology and the British Maternal and Fetal Medicine Society. Frontline Gastroenterology 2021;12:182-187 BMJ 2020